ANALISIS ENERGI PEMADATAN TANAH DI LABORATORIUM - Fakhrul Rozi Yamali; Fadlan Fadlan; Fakhrul Rozi Yamali (Universitas Batanghari, 2017)
The density test for soil in the laboratory can be a mild density test (standard proctor) and a modified density test (modification proctor). Both types of compaction provide different levels of density. This paper aims to analyze the energy produced by both types of compaction. The results show that the compaction modification energy is greater than the standard compaction energy. These results are influenced by the number of layers and the difference of the mass of the pounder on both types of compactionKey words: compaction energy, standard proctor, modified proctor